1992
DOI: 10.3354/meps081163
|View full text |Cite
|
Sign up to set email alerts
|

Water-column nitrate enrichment promotes decline of eelgrass Zostera manna: evidence from seasonal mesocosm experiments

Abstract: We imposed a replicated gradient of water-column nitrate enrichment in large-scale experimental mesocosms to test the response of eelgrass to nitrate loading during the spring and fall growing seasons. In spring, controls without nitrate additions ( < l pM ambient NO3--N) were compared to treatments with pulsed daily additions of low (LOW), moderate (MOD), and high (HIGH) enrichment (ca 3.5, 7.0, and 35.0 pM NO3--N d -', respectively). Under low water exchange simulating quiet embayments, eelgrass growth and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
3
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 38 publications
8
141
3
3
Order By: Relevance
“…5B). Nutrient enrichment of sediment drives plants to increase photosynthetic C fixation to meet the increased demand for C. However, if photosynthetic C fixation in leaf and rhizome tissues cannot meet the increased C demand, stored C in plant leaf tissues may be used to support metabolic processes (Burkholder et al, 1992;Irlandi et al, 2004;Lee and Dunton, 1999). This may have led to the shift in balance between aboveground and belowground biomass in our study.…”
Section: Slow Indicator Responses Of Seagrassesmentioning
confidence: 85%
“…5B). Nutrient enrichment of sediment drives plants to increase photosynthetic C fixation to meet the increased demand for C. However, if photosynthetic C fixation in leaf and rhizome tissues cannot meet the increased C demand, stored C in plant leaf tissues may be used to support metabolic processes (Burkholder et al, 1992;Irlandi et al, 2004;Lee and Dunton, 1999). This may have led to the shift in balance between aboveground and belowground biomass in our study.…”
Section: Slow Indicator Responses Of Seagrassesmentioning
confidence: 85%
“…Several studies have shown that no significant growth response to N enrichment has been reported (Murray et al, 1992), others have argued that increased nitrogen levels often 05p7 induce increased growth and biomass (Short, 1987;Van Lent et al, 1995). In other cases, however, decline in macrophytes was observed as a direct effect of increased nitrogen in the form of nitrate (Burkholder et al, 1992) and ammonium toxicity to submerged aquatic plants has also been given much attention in a few freshwater aquatic plants (Smolders et al, 1996). Furthermore, mesocosm experiments conducted in Denmark revealed thresholds of TN and TP concentrations of 1.2−2 and 130−200 ug·L −1 , respectively, above which there is high probability of losing submerged macrophytes in temperate shallow lakes (Gonzalez Sagrario et al, 2005;Jeppesen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Eutrophication of lakes is a widespread environmental problem (OECD, 1982), and a consequential decline in macrophytes has been recorded over the past three decades (Burkholder et al, 1992;Perrow et al, 1994;Middleboe and Markager, 1997;Melzer, 1999;Tracy et al, 2003;Qin et al, 2005). Although there has been no consensus in explaining this phenomenon, some incidental stresses of eutrophication have been suggested as the causal factors, including overgrowth epiphytes and macroalgae and the associated light reduction, low sediment redox potential, excessive nutrient supply and an absence of an uptake regulation mechanism for certain species (Sand-Jensen, 1977;Phillips et al, 1978;Burkholder et al, 1994;Terrados et al, 1999;Ni, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous 13 studies mainly focused on the effects of high nitrate or ammonium concentrations in the surface water layer (Burkholder et al, 1992;Christianen et al, 2011;Van der Heide et al, 2008;van Katwijk et al, 1997). In a correlative study (Short, 1983b) already suggested that porewater nitrogen concentrations of 10 -100 mmol m -2 were associated with decreasing eelgrass shoot densities.…”
Section: Ammonium Toxicitymentioning
confidence: 99%